DESIGN OF A LEARNING SUPPORT APPLICATION FOR THREE-DIMENSIONAL GEOMETRY FOR 12TH GRADE HIGH SCHOOL STUDENTS - Putri, Nidya
Learning three-dimensional geometry often poses challenges for 12th-grade students due to its abstract nature and difficulty in visualization. This research is motivated by the need for educational media that can facilitate a more interactive and engaging understanding of three-dimensional geometry concepts. The objective of this study is to design and develop a learning application that utilizes digital technology to assist students in comprehending three-dimensional geometry. The design method employs the Garrett framework, which consists of five stages: Strategy, Scope, Structure, Skeleton, and Surface, followed by usability testing to assess the application's ease of use. After the testing phase, iterations were conducted to evaluate the application's performance and the effectiveness of its features, as well as to implement improvements in both areas. The uniqueness of this research lies in the integration of specialized features designed to address common difficulties faced by students in learning three-dimensional geometry. The results of this study provide significant contributions to the development of knowledge, particularly in the fields of mathematics education and educational technology. Additionally, this application can serve as a reference for developing other learning applications with similar features, potentially enhancing the quality of education at various levels. Thus, the developed application not only overcomes the limitations of traditional educational media but also offers a new approach to teaching three-dimensional geometry that can be adapted across different educational levels.